Lima Protocol for Cleft Palate Repair in Cleft and Craniofacial Centre Cipto Mangunkusumo Hospital Indonesia: A Preliminary Study - Bangun, Kristaninta; Halim, Jessica; Tania, Vika (Jurnal Plastik Rekonstruksi, 2022)
Background : The techniques of cleft palate repair has faced significant evolutions. More importantly, no surgical protocol has been significantly associated with lower incidence of post-operative complications such as fistula formation, velopharyngeal insufficiency, or speech hypernasality. As cleft width is a strong predictor of outcomes, The Lima Protocol was introduced to select suitable surgical technique based on the degree of severity measured by palatal index. This article aimed to evaluate the efficacy of the newly established Lima Protocol in lowering post-operative complications in primary cleft palate repair surgery in Cleft and Craniofacial Center, Cipto Mangunkusumo Hospital, Jakarta, Indonesia.Case Presentation : This study is a case series featuring 6 patients with cleft palate treated with primary palatoplasty. Surgical techniques were selected based on the degree of severity measured by Palatal Index. The average age of performing primary palatoplasty was 14 months. 50% of the cases was classified as Veau 2 and the rest was Veau 3. Half of the patients fell into severe category based on Palatal Index and the other half was in moderate group. None of the patients developed fistula formation 3 months post-palatoplasty.Discussion & Conclusion: We confirmed that the 1-flap technique provided adequate closure comparable with the 2-flap technique without risking mucoperiosteal flap necrosis and fistula formation. Using the strengths of different surgical techniques individualized for each case based on the palatal index and grade of severity is indisputably a practical strategy. Trials with longer follow-ups are required to widely implement The Lima Protocol.